PERBAIKAN KUALITAS AIR DENGAN PENGELOLAAN SECARA FISIKA DAN KIMIA. - Yennita Yennita; Mulyadi Mulyadi; Mubarak Mubarak (Program Pascasarjana Universitas Riau, 2007)
Improving of water quality from siak river that have been used for long time by communities around the river for many purposes such as drinking water and washing has been done by implementing various method such as filtration, coagulation, aeration absorption. Each method has specific characteristic and advantages. Filtration with sand and gravels can decrease concentration of total suspended solid, Fe, Mn and organic material (KMnO4). Coagulation with alum (Al2SO4) can decrease TSS Concentration, Fe, Mn, NO3, NO2, KMnO4, coliform and coli fecal. Furthermore, aeration with a oxygen can decrease TSS concentration, TDS, Fe and Mn. While absorption whit active carbon can decrease concentration of TSS, Mn and Fe. After the four methods had been studied, the best result was obtained through combination of four methods (filtration, coagulation, aeration and absorption).